Monetary policy committees in action: Is there room for improvement? - Philipp Maier (Bank of Canada, 2007)
More than 80 central banks use a committee to take monetary policy decisions. The composition of the committee and the structure of the meeting can affect the quality of the decision making. In this paper we review economic, experimental, sociological and psychological studies to identify criteria for the optimal institutional setting of a monetary committee. These include the optimal size of the committee, measures to encourage independent thinking, a relatively informal structure of the meeting, and abilities to identify and evaluate individual members' performances. Using these criteria, we evaluate the composition and operation of monetary policy committees in various central banks. Our findings indicate that e.g. the monetary policy committee of the Bank of England follows committee best-practice, while the committee structure of other major central banks could be improved.
Keywords: C92; D70; E58; 330; Central bank research; Monetary policy framework; Zentralbank; Vorstand; Entscheidung; Geldpolitik